Enhancing our understanding of sport practitioner perspectives on developing effective sporting environments - Mitchell, T.; Sargent Megicks, B.; Gledhill, A. (Journal of Sports Sciences, 2024)
Research has increasingly focused on the environmental features within talent and performance development settings. However, practitioner perspectives on their role in optimizing these environments are scarce. This study aimed to examine practitioner perspectives of the role of the environment, specifically, how they plan, deliver and review (p-D-R) to optimize environmental conditions for athletes. Ten sports practitioners (including managers, coaches and multidisciplinary support staff) took part in semi-structured interviews. Data was analysed using a reflexive thematic analysis and generated themes associated with Planning (Conceptualization, Planning and Meeting Athlete`s Needs), Delivering (Explicit, Implicit, Support, Communication, Holistic Approach) and Reviewing (KPIs, Evaluation & Monitoring, Rolling Review, Review Process). Findings suggest that to offer the best possible experiences to participants, practitioners must have a clear view of their objectives and involve all stakeholders associated with delivery at the planning stage. Much of the delivery aspect aligned with notions of effective TDEs suggesting practitioners had a clear awareness of what works for them in their contexts. Reviewing the environment appeared to be the activity practitioners undertook the least, this may reflect the complex and dynamic nature of the environment in sports settings.